Construction and validation of socio-economic status scale (2020)
The purpose of this study was to validate and determine the psychometrics properties of Teaching Performance Assessment Rating Scale (TPARS) an instrument that is been used in the assessment of teachers in training in University of Ibadan. The TPARS is a 20-item inventory which assesses teaching performance among education students in university of Ibadan. Three research questions were raised to guide the study.The results of the TPARS analysis reveal that the instrument of teaching performance skills comprises of six dimensions namely:Teachers in training preparation, Making Learners Ready and Progression, Communication and Teachers in training pupils interaction, Assignment, Grading Praise and Rewards, Classroom Atmosphere, Subject mastery and Instructional materials and Teachers in training demeanor. The researcher further tested whether the TPARSis tenable using confirmatory factor analysis. The result of Confirmatory Factor Analysis provides a good fit of the data within the hypothesized six-factor model, implying that the TPARS can be subsumed into six domains. Discriminant and Convergence validities were moderate ranging from .31 to .69. Alpha coefficients for six TPARS subscales ranged from .81 to .96, and .79 for the whole scale. The findings highlighted the importance of using indigenous instrument in identification of factors underpinning teaching performance among teachers in trainee. The study recommends the TPARS for other higher institutions to assess their teachers in training so that all higher institutions in Nigeria could have single and uniform instrument for assessing teaching performance skills of student-teacher. This study developed and validated Socio-economic status scale. This study employed a descriptive research design of survey type. The study made use of five-hundred and fifty-four randomly selected individuals from the public and private organisations in Ibadan land. The instrument consists of seven sections; the first section is made up of demographic variables of the participants while the other sections were made up of 45 items related to Socio-economic status issues. Principal component analysis and confirmatory factor analysis supported six factors of the Socio-economic status Scale (SESS). In selecting the items for the final scale, items with the total-item correlation of less than 0.3, those with factor loadings of less than 0.4 and factor loadings of 0.4 on two or more factors were removed. The scale has high internal consistency and adequate construct validity. The subscales of the Socio-economic status Scale (SESS) are Educational History, Housing tenure, Occupation History, Income pattern, Travelling Experience, and Possession of Property and Professional Affiliates that one belongs. Based on the findings of this study, the researcher concluded that the instrument has high internal consistency and adequate construct, concurrent, discriminant and convergent validity and that it can be used to measure SES of any individual. Accurate measurement of the SES of families could be obtained using SESS for future research and SES categorization.